Orthopaedic Diagnoses in the Black Pediatric Population. Issue 6 (15th March 2023) - Bridges, Carla M.; Agarwal, Rashmi; Raney, Ellen M.
Abstract : The Black pediatric population is one that has been historically underserved and continues to have unmet needs. Factors including lack of diversity in orthopaedic studies and in historical standards, such as bone age, may inadvertently lead to inferior care. There are certain conditions in this population for which the practicing orthopaedic surgeon should have a higher degree of suspicion, including slipped capital femoral epiphysis, Blount disease, and postaxial polydactyly. Systemic diseases with higher rates in this population have orthopaedic manifestations, including sickle cell disease, vitamin D deficiency, and obesity. Racial discrepancies in access to prenatal care can have orthopaedic consequences for babies, especially cerebral palsy and myelodysplasia. Racial discrepancy exists in evaluation for nonaccidental trauma. Increased awareness of these issues better prepares practitioners to provide equitable care.